Women's health priorities and interventions. (14th September 2015) - Temmerman, Marleen; Khosla, Rajat; Laski, Laura; Mathews, Zoe; Say, Lale
Abstract : Building on the unfinished agenda, Marleen Temmerman and colleagues elaborate actions needed to improve the health and wellbeing of women and girls around the world